The association between the microbes in the tracheobronchial aspirate fluid and bronchopulmonary dysplasia in preterm infants - Xiao-yan Gao; Yi-heng Dai; Da-zhi Fan; Xiao-yun Xie; Guang-di Yang; Xin Xiao; Ping-ming Gao (Elsevier, 2020)
Objective: The study aimed to evaluate the association between microbes in the lower respiratory tract (LRT) and the srisk for severe bronchopulmonary dysplasia (sBPD) in premature infants. Methods: We conducted a retrospective, single-center study of preterm infants who were admitted to the neonatal intensive care unit (NICU) of Southern Medical University Affiliated Maternal & Child Health Hospital of Foshan, China, between January 2015 and December 2017. The microbes in the LRT were screened by using tracheobronchial aspirate fluid (TAF) culture. Results: One hundred and fifty-five infants were included in the analysis. Among 155 infants, 41 were diagnosed with sBPD, and 114 were diagnosed without sBPD. There were significant differences between infants with and without sBPD in regard to birth weight (BW), gestational age (GA), the duration of endotracheal ventilation and supplemental oxygen. The incidence of retinopathy (ROP) and sepsis was higher in the sBPD infants than in the infants without sBPD. There was a difference in the detection rate of Gram-negative bacteria (GNB) between the two groups. Stenotrophomonas maltophilia and Klebsiella pneumoniae were mainly detected in TAF. Conclusions: The LRT microbes were different between infants with and without sBPD, and GNB is more frequently detected in sBPD infants.